2018
DOI: 10.1161/jaha.118.008920
|View full text |Cite
|
Sign up to set email alerts
|

Statin Eligibility, Coronary Artery Calcium, and Subsequent Cardiovascular Events According to the 2016 United States Preventive Services Task Force (USPSTF) Statin Guidelines: MESA (Multi‐Ethnic Study of Atherosclerosis)

Abstract: BackgroundThe potential impact of the 2016 United States Preventive Services Task Force (USPSTF) guidelines on statins for primary prevention of atherosclerotic cardiovascular disease (ASCVD) warrants further analysis.Methods and ResultsWe studied participants from MESA (Multi‐Ethnic Study of Atherosclerosis) aged 40 to 75 years and not on statins. We compared statin eligibility at baseline (2000–2002) and over follow‐up between USPSTF and the 2013 American College of Cardiology/American Heart Association (ACC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(26 reference statements)
2
2
0
Order By: Relevance
“…CAC screening using nongated CT has become an increasingly available and consistently reproducible means for stratifying ASCVD risk and guiding statin therapy in individuals with equivocal ASCVD risk scores. [24][25][26] As has been demonstrated in previous studies, our study additionally highlights the effective use of LDCT in not only identifying CAC, but also in beneficially impacting statin decisions in the high-risk smoking population. [24][25][26] Our results also showed LDCT missed CAC in participants, the majority of which were already on a statin, and only 1 nonstatin individual benefited from additional CAC reporting.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…CAC screening using nongated CT has become an increasingly available and consistently reproducible means for stratifying ASCVD risk and guiding statin therapy in individuals with equivocal ASCVD risk scores. [24][25][26] As has been demonstrated in previous studies, our study additionally highlights the effective use of LDCT in not only identifying CAC, but also in beneficially impacting statin decisions in the high-risk smoking population. [24][25][26] Our results also showed LDCT missed CAC in participants, the majority of which were already on a statin, and only 1 nonstatin individual benefited from additional CAC reporting.…”
Section: Discussionsupporting
confidence: 80%
“…[24][25][26] As has been demonstrated in previous studies, our study additionally highlights the effective use of LDCT in not only identifying CAC, but also in beneficially impacting statin decisions in the high-risk smoking population. [24][25][26] Our results also showed LDCT missed CAC in participants, the majority of which were already on a statin, and only 1 nonstatin individual benefited from additional CAC reporting. CAC scoring on LDCT should be an adjunct, not a substitute, for ASCVD risk stratification to help guide statin management.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is reported that the USPSTF statin guidelines resulted in a 15% decrease in statin eligibility when compared to the 2013 ACC/AHA guidelines in the atherosclerosis patients who were not on statin therapy [ 29 ]. Consistent with these findings in the present study also, we observed a significantly higher number of patients ineligible for statin therapy according to the USPSTF guidelines as compared to the 2013 ACC/AHA guidelines.…”
Section: Discussionmentioning
confidence: 99%